Performance, Slack, and Risk Taking in Organizational Decision Making - Singh, Jitendra V. (Academy of Management Journal, 1986)
This research paper investigates the relationship between organizational performance and risk taking in organizational decision making. A complex model is proposed in which the direct relationship, which is triggered by performance below acceptable levels, is negative, but the indirect relationships, which are mediated by organizational slack and decentralization, are positive. A test of the model for a cross-sectional sample of firms shows general support for the model. The findings have implications for theories that view change as arising from stable organizational processes.